Synthesis of PANi-TiO2 composite and preparation of Ti/PANi-TiO2 electrode for electrochemical study in brewery wastewater - Duyen, Nguyen The; Duyen, Mai Thi; Thanh Thuy, Mai Thi; Van Anh, Nguyen Thi; Binh, Phan Thi (Vietnam Journal of Chemistry, 2017)
PANi-TiO2 composites are successfully by synthesized by chemical method using TiO2 from 30 to 80 wt % to aniline during polymerization process for improving their material properties. Their conductivity was characterized by I-E curves among them the highest one (13.37 mS/cm) reached by using 40 wt % TiO2. Their paste form was made by using chitosan acetic acid solution as binder agent for preparing Ti/PANi-TiO2 electrode which measured in brewery wastewater by electrochemical impedance. It was found an electrical equivalent circuit with 6 elements including solution resistance Rs, capacitance Cf and resistance Rf of composite electrodes, adsorption capacitance Cad, charge transfer resistance Rct and Warburg diffusion element W. It was found the lowest charge transfer resistance of 165.8 Ω in the case of using 40 wt % TiO2. The SEM images explained that the composite existed in uniform fiber with diameter size of nano range. It was found the presence of TiO2 and PANi in material structure by X-ray diffraction and IR-spectra analysis, respectively. Keywords. Ti/PANi-TiO2 electrode, impedance spectroscopy, substrate electrolyte.